Inovasi Manajemen Perpustakaan - Prita Yutika Kalmania; Abdul Kosim; Kasja Eki Waluyo (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to investigate and describe library management innovations at Madrasah Aliyah Negeri 2 Karawang with a focus on innovation research studies in: planning the procurement of library collections, classifying library collections, library services and evaluating and monitoring libraries. The method used in this research is descriptive qualitative. The research subjects were the head of the library, library managers, teachers and students. Data collection techniques used are interview, observation and documentation techniques. Data analysis procedures are data reduction, data display, and data verification. The results showed that there were innovations in planning, classifying, serving, evaluating and monitoring.